The Effectiveness of Emotion Regulation Training on Reducing Aggressive and Oppositional Behaviors Among Children Aged 4 to 6 Years - Maryam Sedighi; Ghasem Naziry (Gonabad University of Medical Sciences, 2020)
Background: Emotion regulation is necessary for psychological wellbeing and social functioning. The present study aimed to evaluate the effectiveness of emotion regulation skills training on reducing aggressive and oppositional behaviors in children (4-6 years old) in Shiraz, City, Iran during the fall and winter of 2018-19. Methods: This was quasi-experimental study with pre-test & posttest design and controlgroup.The current studychr('39')s statistical population consisted of 26 children with symptoms of aggressive and oppositional behaviour through the Child Symptom Inventory (CSI-4) and the Seyedi questionnaire for aggression. Among these people, a purposeful sampling method was used to select 26 individuals (13 to a control group and 13 individuals assigned to an experimental group). The experimental group participated in 28, 30-45-minute emotion regulation training sessions from a programme called DECA-P2, whereas the control group received no treatment. A posttest was conducted after the sessions were done. The Child Symptom Inventory-4(CSI-4) and Aggression questionnaire were used to collect the data. Data were analyzed MANCOVA by using SPSS V. 23 software.  Results: Results of covariance analysis showed that emotion regulation training with the DECA-P2 approach was effective in reducing aggressive and oppositional behavior among children (P<0.01). Conclusion: Considering the effectiveness of emotion regulation training (the DECA-P2 approach) in reducing the aggressive and oppositional behaviors among children, we recommended that authorities apply this training to reduce children's maladaptive behaviors and prepare them for the next emotional and social development stages.